'My Neighbour Drinks Clean Water, While I Continue To Suffer': An Analysis of the Intra-Community Impacts of a Rural Water Supply Project in Mozambique. Issue 8 (3rd August 2017) - Van Houweling, Emily; Hall, Ralph; Carzolio, Marcos; Vance, Eric
ABSTRACT: Rural water planners assume the positive impacts of community water projects are spread evenly across the population. We test this assumption by looking at the distribution of benefits within communities that received handpumps in rural Mozambique. Using survey and qualitative data we analyse the characteristics of those groups who benefited from the handpumps and also explore household decision-making processes. Handpump use was determined by distance, availability of other sources, perceptions of water quality, political affiliation, and wealth. We argue that the handpumps reinforced existing social divisions related to income and political affiliation and created new geographic divisions within communities.